PENGARUH VARIASI MENU DAN PENGALAMAN KONSUMEN TERHADAP MINAT BERKUNJUNG KEMBALI YANG DIMODERASI OLEH KEPUASAN KONSUMEN NASI UDUK PERMATA PASIR PENGARAIAN - Wulandari, Afrilla; Seprini, Seprini (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to determine the effect of menu variety and customer experience on revisit intention, moderated by customer satisfaction at Nasi Uduk Permata Pasir Pengaraian. The study population was customers of Nasi Uduk Permata Pasir Pengaraian. A sample size of 100 respondents was selected using accidental sampling. The independent variables in this study were menu variety and customer experience, with satisfaction as the moderating variable, and the dependent variable was revisit intention. Data analysis techniques used were Structural Equating Modeling (SEM PLS) and Smart PLS. The results showed that menu variety had a positive and significant effect on customer satisfaction, customer experience had a positive and significant effect on customer satisfaction, menu variety had a positive but insignificant effect on consumer revisit intention, consumer experience had a negative but insignificant effect on consumer revisit intention, and consumer satisfaction had a positive and significant effect on consumer revisit intention.